(untitled) (Damascus University Journal for the economic and Political sciences, 2022)
The aim of the research is to shed light on the availability of the elements needed for implementing the responsibility accounting system in the Syrian government banks, and how to classify costs and revenues and then allocate them to the responsibility centers in the departments, instead of measuring them at the bank’s overall level. To determine the reflection of that on the performance of banks from the viewpoint of employees in the bank, a questionnaire was distributed to employees to obtain their opinions during the first quarter of 2020. The researcher reached several results, the most important of which are: the Syrian government banks define responsibility centers at their various administrative levels and provide an accurate description of these centers. They classify costs and revenues according to the centers of responsibility. The Syrian government banks achieve compatibility between the goals specified in the plans and strategies and the way in which work is carried out, where workers participate in the various responsibility centers to prepare the planned performance standards and the scientific method is adopted to define the performance standards for each responsibility center.